Makna Komunikasi Simbolik di Kalangan Pengguna Tato Kota Bandung - Gumgum Gumilar (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
The aim of this research is to give result qualitative data through phenomenological approach and symbolic interaction about tattoos among its users. The focus of this research includes its development, motivation and the process of making tattoo, symbolic meaning and impression management were done in communication among tattoo users in Bandung. The research informant in this research was 24 tattoo permanent users with using purposive sampling. The data collecting used in this research were observation, depth interview and documentation/archive study. The result of this research showed that tattoo users could be categorized based on: Reasons, contact and immanent tattoo users; motive, past and future orientation tattoo users; design, classical, modern, and contemporary tattoo users; Tattoo placing, open and close tattoo users, and studio preferences, safe and risk tattoo users. In addition, tattoo artists could be categorized in; the period of profession, past and current tattoo artist; the tool in making tattoo, traditional and modern; the process of tattooing, safe and risk; skills, independent learner artist and special learning learner artist; the place of tattoo making, professional and street vendor artist.